Perlindungan Saksi dalam Sistem Peradilan Pidana - Asrianto Zainal (Institut Agama Islam Negeri (IAIN) Kendari, 2008)
This study aims to describe the protection of witnesses in the criminal justice process by using qualitative approach data obtained through literature study results analysis indicates that the witness including victim witness is a party that contributes greatly in the criminal justice process, therefore, should have the protection as suspects and defendants so that their testimony can be given well so that with the guarantee then the judiciary can be implemented properly so that not only can achieve procedural but also substantive justice.